Determination of concrete fracture parameters based on peak-load method with diagonal split-tension cubes - Ince, Ragip (Pergamon-Elsevier Science Ltd, 2012)
Using the boundary element method, unnotched and notched split tension-cubes were analyzed by applying compressive forces in the diagonal planes. The maximum tensile stress of the unnotched diagonal cubes and the linear elastic fracture mechanics formulas of the notched diagonal cubes, K-I, CMOD and COD profile, were determined for different load-distributed widths. Subsequently, to investigate the extent to which the diagonal split-cube tests could simulate the fracture behavior of concrete, four series of tests were performed. Finally, the advantages of diagonal splitting cubes are discussed in comparison to other splitting specimens. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Splitting test; Two-parameter model; Peak-load method; Boundary element method